Evaluating the impact of interprofessional training wards on patient satisfaction and clinical outcomes: a mixed-methods analysis - Schlosser-Hupf, Sophie; Aichner, Elisabeth; Meier, Marcus; Albaladejo-Fuertes, Sheila; Ruttmann, Kirstin; Rusch, Sophia; Michels, Bernhard; Mehrl, Alexander; Kunst, Claudia; Schmid, Stephan; Müller, Martina (Frontiers in Medicine, 2024)
Introduction Interprofessional teamwork is pivotal in modern healthcare, prompting the establishment of interprofessional training wards since 1996. While these wards serve as hubs for optimizing healthcare professional collaboration and communication, research into patient outcomes remains notably sparse and geographically limited, predominantly examining patient satisfaction and sparingly exploring other metrics like mortality or self-discharge rates. This study seeks to bridge this gap, comparing patient outcomes in interprofessional training wards and conventional wards under the hypothesis that the former offers no disadvantage to patient outcomes. Materials and methods We explored patient outcomes within an interprofessional student ward called A-STAR at a University Hospital from October 2019 to December 2022. Engaging with patients discharged between May 2021 and April 2022, we utilized digital and paper-based anonymous questionnaires, catering to patient preference, to gather pertinent data. Results Analysis of outcomes for 1,482 A-STAR (interprofessional student ward) and 5,752 conventional ward patients revealed noteworthy findings. A-STAR patients tended to be younger (59 vs. 61 years, p < 0.01) and more frequently male (73.5% vs. 70.4%, p = 0.025). Vital clinical outcomes, such as discharges against medical advice, complication-driven readmissions, and ICU transfers, were statistically similar between groups, as were mortality rates (1.2% vs. 1.3%, p = 0.468). A-STAR demonstrated high patient satisfaction, underscored by positive reflections on team competence, ward atmosphere, and responsiveness to concerns, emphasizing the value placed on interprofessional collaboration. Patient narratives commended team kindness, lucid explanations, and proactive involvement. Discussion This data collectively underscores the safety and reliability of patient care within training wards, affirming that patients can trust the care provided in these settings. Patients on the interprofessional ward demonstrated high satisfaction levels: 96.7% appreciated the atmosphere and conduct of ward rounds. In comparison, 98.3% were satisfied with the discussion and information about their treatment during their hospital stay.